THE CONCEPT OF RE-DEMOCRACY IN THE ANALYSIS OF CONSTITUTIONAL COURT DECISION NO. 135/PUU-XXII/2024 AND THE DISCUSSION OF CLOSED PROPORTIONALITY - Dedi Mulyadi; Leny Megawati; Salsa Octaviani Suryanto; Fuji Raihan Azhari Kusworo; Ardelia Lananda; Ira Permatasari (Proceeding International Conference on Social Sciences, 2026)
Re-democracy is an idea to revive a more substantial democracy by emphasising people's representation, public participation, and strengthening deliberative spaces. Therefore, this study is important to see the opportunities for reconstructing Indonesia's political system to be more representative and inclusive. This research uses a normative juridical approach by analysing Constitutional Court Decision Number 135/PUU-XXII/2025 and public discourse on the closed proportional election system. The ruling separates national and local elections by a minimum interval of two years, based on technical complexity, personal and institutional fatigue, and declining voter participation in simultaneous elections. This policy has reignited the debate on closed proportional representation, which is considered capable of restoring the essence of substantive democracy through the mechanism of aggregating the aspirations of the people. This research identifies the legal, political, and social consequences of Constitutional Court Decision Number 135/PUU-XXII/2024 and the discourse on the return of the closed proportional system, as well as the issues and efforts to realise the aggregation of public aspirations through re-democracy. The purpose of this research is to examine the legal and political implications of the Constitutional Court's decision and the debate on the closed proportional system ahead of the 2029 elections in order to strengthen re-democracy. Thus, Constitutional Court Decision No. 135/PUU- XXI/2024 and the discourse on closed proportional representation reflect the need for re-democracy to strengthen the aggregation of public aspirations in building a more representative and substantive political system.